Agro-morphological characterisation of a collection of Cynodon - Wouw, M. van de; Mohammed, J.; Jorge, M.A.B.; Hanson, Jean (2009)
Ninety–eight accessions of Cynodon, belonging to 4 different species and including several hybrids were haracterised using a set of 23 agro–morphological characters. The collection included both collections from natural populations and breeding lines, selected among siblings of open–pollinated plants. Morphological and agronomic traits were assessed and multivariate analysis was applied to cluster similar accessions. The research identified a group of turf grass type accessions, a group consisting of the accessions of C. aethiopicus and a main group of C. dactylon and C. nlemfuensis. Clustering within this main group of 89 accessions revealed 7 sub– groups of similar accessions differentiated mostly by the length of the leaf, spikelet colour and days to 50% flowering. Only the number of stolons and days to first flowering did not show significant differences among clusters. Three accessions were so different that they could not be assigned to any cluster. C. dactylon and C. nemfuensis were very similar, with a large overlap in diversity of characters. The breeding lines were very variable and were present in 6 out of 7 clusters, demonstrating that the progeny of a limited number of accessions provided almost as much variation as the accessions collected from natural populations.